Health disparity: implication for coping strategy and perceived stress among women in Gbagi multi-ethnic market - Ibadan, metropolis (2014)
Market women are low income earners and therefore majority of them are often unable to afford medical expenses. Yet, most government healthcare interventions schemes have failed to address the health concern of this group leading to high disparity in their health status and their counterparts who are high income earners. In view of this, the current study investigated Health disparity: Implication for Coping Strategy and Perceived Stress among women in Gbagi multi-ethnic market in Ibadan Metropolis, Oyo State, Nigeria. Market women who were 249 were conveniently sampled. Their age ranged from 31 to 51 years. A structured questionnaire comprising of socio-demographic variables and measures of perceived stress, coping and health disparity was used to collect data. The hypotheses were tested using independent t-test, multiple regression analysis and one-way analysis of variance. There was significant influence of coping on health disparity of market women (t(247)=-2.27, p<.05) among participants with high coping (X =25.85) reporting higher level of health disparity than those with low coping (X =24.53). Perceived stress and coping influenced 33% pf health disparity. However, only coping (β=0.31; t=5.06, p<.001) showed significant independent influence on health disparity. There was also significant influence of family type on health disparity (t(236)=-2.10, p<.05). Participants from nuclear families (X =25.87) significantly reported higher level of health disparity than those from extended families (X =24.63). There was significant influence of education status on health disparity F(6,248)=7.22; p<.001). Age also had significant influence on health disparity F(3,248) = 7.77; p<.001). It was concluded that perceived stress and coping strategy had significant influence on health disparity. This finding has implications for well-being and community health. It was suggested to health administrators to include market women in their health promotion policy